A Soft Systems Methodology Application to Promote the Multidimensional Model of e-Government Project Management in Indonesia’s Construction Services - Chomistriana Dewi; Mulyono T. Agus; Najid Najid (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
The Integrated Construction Services Information System (ICSIS) project is one of the Indonesian government's initiatives to meet public demand for better construction business services. Despite being in operation for approximately 6 (six) years, ICSIS performs poorly. Fragmented business processes, noninteroperable systems, and unaccountable data all demonstrate poor performance in this regard. With all the best efforts, ICSIS only reaches 12% of the total target users. This paper discusses a problem-structuring approach to problem analysis and comprehension, as well as the critical factors to consider through stakeholder interaction. From various perspectives, the results of this structuring phase using literature study, comparative analysis and soft systems methodology indicate that multidimensional factors must be considered in order to achieve the expected ICSIS values. This technique assists decision makers in developing a multidimensional model in ICSIS project management with the goal of fostering more dependable and long-term e-government in the construction services.